Assédio sexual contra mulheres em transporte público: uma análise discursivo-crítica de notícias do jornal on-line A gazeta - Silva, Marta Aguiar da (2022)
Sexual harassment in public transportation is a socio-cultural problem, which frightens and embarrasses women through unwanted approaches of sexual imprint. The media can reinforce these actions by encouraging the objectification of the female body and naturalizing male criminal behavior. As a result, readers may form wrong mental models about sexual harassment in public spaces and its victims and may be induced to evoke constructed sexist interpretations when reading news. The need to discuss the influence of the media discourse on the problem of sexual harassment against women due to the relevance of the theme, therefore, justifies this research. The objective of this work is to analyze linguistic-discursive strategies in news, published in the online newspaper A Gazeta, about women victims of sexual harassment in public transportation, and if the linguistic-discursive structures work as strategies of ideology which can be used by journalistic institutions to normalize violent actions. The qualitative methodology includes the collection and selection of news, mainly using the Critical Discourse Analysis (CDA) approach by Teun A. van Dijk (2017 [2011], 2012 [2008], 2011, 2005, 2001, 1999, 1992, 1990, 1980). Considering the multidisciplinary character of the CDA, we also discuss the social issue and the journalistic media. To address sexual harassment, we punctuate about gender relations; women and men in social spaces; a survey of national and Latin American works on the subject; Brazilian and international laws; and data from Instituto Patrícia Galvão/Locomotiva (2019; 2021) and the State Secretariat for Public Security and Social Defense (SESP, 2022). For this, we used the works of Scott (1995), Saffioti (2004), Bourdieu (2002), Biroli (2018), Paul (2016), Butler (2003), among others. To approach the communication vehicle, we present a historical overview of the newspaper A Gazeta. We also consider changes in journalism, characteristics of the online news genre and violence against women in the newspaper A Gazeta. In this discussion, authors such as Bakhtin (2011), Lage (1993), Hall et al. (1993) Traquina (2008); Jorge (2013), Xavier (2010), Natale (2015; 2019; 2020), Tomazi (2019; 2020) and others were fundamental. The result of the analysis of the news indicates positive aspects, such as: topicalizing, in the headlines, the advisor and the crime; represent women as victims and identify the social action addressed, sexual harassment, as a crime of sexual harassment; give victims a voice; and addresses feminist and legal knowledge. However, the negative aspects are the majority: tendency to use headlines with macro propositions in the passive that erase important social actors; the representation of women is associated with the places where they were going, so there is a less negative representation, for example, for women who walk recurrently and arm themselves to try to react to the crime; Women representatives of Justice and Public Security can be given a voice because of their higher hierarchical position as judge and delegates. In addition, the newspaper fails to promote a debate on the subject when it legitimizes the opinion of a law professor by choosing to exclude legal information from the news. In this way, these negative aspects can influence the construction, maintenance and reproduction of sexist ideologies and make no contribution to preventing and/or ending gender violence